2016
DOI: 10.1017/s0033291716001586
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional approach to impulsivity in Parkinson's disease: measurement and structural invariance of the UPPS Impulsive Behaviour Scale

Abstract: The questionnaire appears to function comparably across patients and controls. Thus, group comparisons on the questionnaire can be considered valid. Mean differences between groups on the dimensions of impulsivity may reflect executive impairments and/or abnormal reward processing in patients with PD, which may lead to risky behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 49 publications
(63 reference statements)
2
17
1
Order By: Relevance
“…Our results emphasize that impulsive behavioral changes occur in PD, regardless of ICB status. Indeed, the LASSO analysis reveals most questions distinguishing PD from HCs that align with the changes to attention or inhibitory control, as demonstrated by high ratings on questions such as: “I don’t ‘pay attention’,” “I (don’t) plan tasks carefully,” “I am (not) self‐controlled,” and “I buy things on impulse.” Although the Urgency‐Premeditation‐Perseverance‐Sensation seeking Impulsive Behavior Scale (UPPS) measures different dimensions of impulsivity than the BIS‐11, our findings align well with the overall findings from a study that found that subjects with PD had lower premeditation and greater risk taking than HCs 66 . While it is difficult to compare BIS‐11 findings, we believe that the changes in self‐control and cognitive complexity agree with this finding.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results emphasize that impulsive behavioral changes occur in PD, regardless of ICB status. Indeed, the LASSO analysis reveals most questions distinguishing PD from HCs that align with the changes to attention or inhibitory control, as demonstrated by high ratings on questions such as: “I don’t ‘pay attention’,” “I (don’t) plan tasks carefully,” “I am (not) self‐controlled,” and “I buy things on impulse.” Although the Urgency‐Premeditation‐Perseverance‐Sensation seeking Impulsive Behavior Scale (UPPS) measures different dimensions of impulsivity than the BIS‐11, our findings align well with the overall findings from a study that found that subjects with PD had lower premeditation and greater risk taking than HCs 66 . While it is difficult to compare BIS‐11 findings, we believe that the changes in self‐control and cognitive complexity agree with this finding.…”
Section: Discussionsupporting
confidence: 83%
“…Although patients with dementia were excluded, in the absence of formal neuropsychological testing, it is possible that some patients may have met criteria for mild cognitive impairment. A previous study found that there was no difference in BIS‐11 scores and domain scores between PD and PD‐MCI patients 66 . We hypothesize that self‐reported problems with attention in this population with PD may reflect early dysexecutive symptoms, of which the MoCA screening is heavily weighted.…”
Section: Discussionmentioning
confidence: 68%
“…Lower perseverance was reported in people with obsessive-compulsive symptoms, compulsive buying (74-77), bulimia (78), and self-injury behavior (79). One study found lower perseverance in PD patients with and without ICD (7). PD-ICD patients in our sample did not manifest higher levels of Urgency, which represents the aspect of emotional impulsivity.…”
Section: Discussioncontrasting
confidence: 38%
“…Research using self-reported methods concluded that people with certain personality traits are in higher risk of developing ICD. Specifically, associations between ICD and higher novelty/sensation seeking, compulsivity, depression, and anxiety were found (3,(7)(8)(9). Impulsive personal traits have been previously associated with ICD in PD.…”
Section: Introductionmentioning
confidence: 79%
“…However studies in PD in the absence of clinically defined impulse control disorder are lacking and even the ones with late stage ICD [49,50] lack simultaneous assessment of all impulsivity domains. Personality traits based scales [51] such as the Urgency-Premeditation-Perseverance-Sensation seeking Impulsive Behaviour Scale, are clinically useful, but do not address the neurobehavioural dimensions investigated in our study.…”
Section: Discussionmentioning
confidence: 99%